Magnesium alleviates aluminum toxicity in wheat and maize seedlings - Vanderson Modolon Duart; Eduardo Fávero Caires; Érica Cristina de Oliveira; Rodrigo Rodrigues Matiello (Technology in Agronomy)
Aluminum (Al) toxicity inhibits root growth, affecting the ability of plants to absorb water and nutrients. Although magnesium (Mg) can decrease Al phytotoxicity, its effect on plant root growth in minimal solution containing calcium (Ca) and Al is not yet known. We evaluated the root length of wheat and maize genotypes with different sensitivities to Al in minimal solution containing different combinations of Al and Mg: (i) control (without Al and Mg); (ii) with 0.15 mmolc L−1 of Al; (iii) with 0.15 mmolc L−1 of Al plus 2 mmolc L−1 of Mg; and (iv) with 0.15 mmolc L−1 Al plus 10 mmolc L−1 of Mg. By measuring the difference in root length, we found that the minimum solution method with 0.15 mmolc L−1 of Al was efficient to classify the wheat and maize genotypes tolerance to Al. The Al-sensitive wheat and maize genotypes showed a higher reduction in root length compared to the Al-tolerant genotypes when subjected to a solution containing Al. The addition of Mg in the solution, especially at higher concentration (10 mmolc L−1 of Mg), effectively alleviated Al toxicity and favored root growth of wheat and maize genotypes. Our results suggest that Mg alleviates the toxic effects of Al on root growth of wheat and maize genotypes in minimal solution containing Ca and Al and that both the use of Al-tolerant wheat and maize genotypes and the maintenance of adequate levels of Mg in the soil solution are important strategies to alleviate Al toxicity to plants.